The role of art and art education in spreading environmental awareness in the school environment - Al-Besany, Hiba Ismail Adel (Journal of Educational and Psychological Sciences, 2021)
Art is an expression and a cultural, educational and social message, the language of civilization, the most important form of it, and through it we understand societies and study their development, it is a civilized production and a cultural expression that has conditions and laws that distinguish it from other production or regular expression. Art is an unusual expression that is an eye-catching expression or production that is sensational. Art must reflect taste, science and mission in order to be an art aimed at all senses, emotions, minds and human perceptions throughout the ages and across different cultures.Art education is one of the positive entry points for providing students with positive values ​​and attitudes towards protecting and improving the environmentIn order to prepare a generation that is aware of its problems and the importance of interaction between it and its environment, where environmental education and art education are involved in containing basic concepts that can be put into practice in teaching, art education is one of the areas that can achieve the goals of environmental education and clarify its concepts effectively.Through this article, we tried to highlight the importance of art and art education in spreading environmental awareness, especially in light of the spread of the epidemic of the Corona Virus Covid-19, and what art education can offer to spread environmental awareness through the practice of learners of this subject in various phases in the school environment.
Keywords: art; art education; environmental awareness; school environment